2020
DOI: 10.1017/s1047951120001778
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac workup and monitoring in hospitalised children with COVID- 19

Abstract: AbstractApproximately, 1.7 million individuals in the United States have been infected with SARS-CoV-2, the virus responsible for the novel coronavirus disease-2019 (COVID-19). This has disproportionately impacted adults, but many children have been infected and hospitalised as well. To date, there is not much information published addressing the cardiac workup and monitoring of children with COVID-19. Here, we share the approach to the cardiac workup and monitoring utilised at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…3,4 At our institution, the serology testing does not differentiate between immunoglobulin M and immunoglobulin G; thus, a positive serology test result does not clearly define a resolved infection. ECGs were routinely obtained after admission according to our institution's guidelines for workup of all patients with MIS-C. 6 First-degree AVB on the ECG was defined as a PR interval on a surface ECG .200 milliseconds without associated disruption of atrial-to-ventricular conduction. 7 All ECGs were read by a pediatric cardiologist using electronic calipers.…”
Section: Methodsmentioning
confidence: 99%
“…3,4 At our institution, the serology testing does not differentiate between immunoglobulin M and immunoglobulin G; thus, a positive serology test result does not clearly define a resolved infection. ECGs were routinely obtained after admission according to our institution's guidelines for workup of all patients with MIS-C. 6 First-degree AVB on the ECG was defined as a PR interval on a surface ECG .200 milliseconds without associated disruption of atrial-to-ventricular conduction. 7 All ECGs were read by a pediatric cardiologist using electronic calipers.…”
Section: Methodsmentioning
confidence: 99%
“…Should any cardiac concerns arise based on history, exam, or other clinical findings, an ECG should be performed, and cardiology consulted, with performance of echocardiography left to the discretion of the consulting cardiologist. 19 Patients with suspected multi-system inflammatory syndrome in children should undergo more complete cardiac workup based on institutional protocol. This protocol was based on expert opinion and was not uniformly implemented at our institution at the time.…”
Section: Discussionmentioning
confidence: 99%
“…This direct viral invasion, postulated to be caused by the binding of the virus to angiotensin-converting enzyme 2 (ACE2) receptors on the cardiac surface, is based on previous studies that found viral RNA in 35% of myocardial infarctions in people infected with another coronavirus (SARS-CoV). This finding was reinforced in a publication in 2005 ( 5 ). Another more recent study ( 6 ) corroborates this hypothesis, with post-mortem findings in cardiac tissue of spherical viral particles on electron microscopy and viral RNA, confirmed by SARS reverse transcriptase-polymerase chain reaction.…”
Section: Pathogenesis Of Cardiovascular Injury Caused By Sars-cov-2mentioning
confidence: 69%
“…In addition, some studies have reinforced the importance of immune-mediated injury in causing damage to the cardiovascular system. This is secondary to the excessive release of cytokines or deregulation of T cells generated by the presence of the virus, resulting in microvascular damage and endothelial dysfunction ( 5 , 9 - 11 ). Animal studies have also shown that elevated cytokines and inflammatory mediators led to decreased cardiac contractility, possibly mediated by calcium-dependent pathways ( 12 - 14 ).…”
Section: Pathogenesis Of Cardiovascular Injury Caused By Sars-cov-2mentioning
confidence: 99%